2013
DOI: 10.1177/0260106014563446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic powder tablet on carotid intima-media thickness in patients with coronary artery disease

Abstract: The results suggest that dry garlic powder tablet is superior to placebo in prevention of CIMT progression in patients with CAD and may be considered as an adjunct treatment for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…It was shown in 2-year double-blinded placebo-controlled trial that Allicor administration leads to cIMT reduction by -0.022mm per year while in placebo group the progression of cIMT was observed with mean annual rate +0.015mm (p < 0.001) (Orekhov et al, 2013;Karagodin et al, 2016b). Another study of garlic powder tablets efficacy on carotid atherosclerosis showed the similar beneficial data, cIMT dynamics differed significantly between verum and placebo groups (p < 0.001): 3-month cIMT reduction -0.009mm in garlic-administrated group vs. 3-months cIMT progression +0.004mm in placebo-administrated group; only preliminary results of this study were published for this moment (Mahdavi-Roshan et al, 2013). An important area of research is the correction of atherosclerotic changes in postmenopausal women.…”
Section: Potential Direct Anti-atherosclerotic Efficacy Of Medicinal mentioning
confidence: 59%
See 1 more Smart Citation
“…It was shown in 2-year double-blinded placebo-controlled trial that Allicor administration leads to cIMT reduction by -0.022mm per year while in placebo group the progression of cIMT was observed with mean annual rate +0.015mm (p < 0.001) (Orekhov et al, 2013;Karagodin et al, 2016b). Another study of garlic powder tablets efficacy on carotid atherosclerosis showed the similar beneficial data, cIMT dynamics differed significantly between verum and placebo groups (p < 0.001): 3-month cIMT reduction -0.009mm in garlic-administrated group vs. 3-months cIMT progression +0.004mm in placebo-administrated group; only preliminary results of this study were published for this moment (Mahdavi-Roshan et al, 2013). An important area of research is the correction of atherosclerotic changes in postmenopausal women.…”
Section: Potential Direct Anti-atherosclerotic Efficacy Of Medicinal mentioning
confidence: 59%
“…Medicinal plants facilitate the treatment of atherosclerosis using different pathway and various mechanisms of the action, a number of medicinal plants have prospects for the prevention or treatment of atherosclerosis. However, direct anti-atherosclerosis activity of preparations based on garlic powder was studied wider than others natural products, their ameliorating effect on the progression of cIMT was proved in randomized double-blinded placebo-controlled trials, registrated on https://clinicaltrials.gov/ (Hodis et al, 2011;Mahdavi-Roshan et al, 2013;Karagodin et al, 2016aKaragodin et al, 2016b. Garlic preparations have the most interesting and obvious cardio-protective properties since garlic is able to ameliorate the blood lipids profile by inhibiting cholesterol biosynthesis, reducing of LDL, modulate arterial hypertension, and inhibit platelet aggregation (Sobenin et al, 2008a;Sobenin et al, 2008b;Sobenin et al, 2009;Jung et al, 2014;Mahdavi-Roshan et al, 2016;Myasoedova et al, 2016;Villa et al, 2017;Choudhary et al, 2018;Sathyapalan et al, 2018;Panahi et al, 2018;Xu et al, 2018;Sedaghat et al, 2019;Adibian et al, 2019;Adab et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For hypercholesterolemia, the reported effects of garlic are small and may be of no clinical relevance [28]. However, the question is under discussion [29]; therefore, reliability of published reports is critical, the more so as the literature is abundant today. Some results obtained in vitro or ex vivo by the same researchers, such as anti-…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a systemic disease responsible for most incidences of CVD s and stroke [5]. Atherosclerosis is a complex phenomenon that is the main cause of coronary artery disease, which can be illustrated an excess of fibro-fatty substance, or the accumulation of atheroma plaques, is an inflammatory response toward arterial wall damage [6,7]. Exposure to cigarette smoke is one of the main risk factors toward the early development of atherosclerosis and other CVD complications.…”
Section: Introductionmentioning
confidence: 99%